EDUKASI PENCEGAHAN WASTING DI WILAYAH POLINDES KEMUNING I DESA LOA LEPU TENGGARONG SEBERANG KUTAI KARTANEGARA - Mareta, Rindha; Haryanti, Deva Aprilia; Sisilia, Helma; Ulo, Kartina; Hanipah, Nur; Sari, Qayla; Cahyaningrum, Sekar Nova; Wahyuningrum, Sella; Putri, Siska Amilistiana Eka (P3M Universitas Aisyiyah Surakarta, 2024)
Nutritional and health problems, especially in toddlers, can be prevented through educational activities provided through posyandu activities. Nutrition education is very important for mothers who have toddlers so they can develop knowledge, skills and choose food ingredients and present a balanced healthy nutrition menu. This community service activity was carried out for mothers of thin toddlers in particular and Posyandu/Polindes Kemuning II RT 02 cadres in Loa Lepu Village, Tenggarong District opposite. Wasting is an important health problem because it has a big impact because it involves the quality of human resources in the future. Wasting itself is a combination of the terms wasting and wasting which is based on an index of body weight for length/(BB/BB) or height (BB/TB) with a threshold (Z-score) < -2 elementary schools. The purpose of this service activity is to increase the knowledge of parents of toddlers regarding the prevention of wasting that occurs in toddlers so that they can improve the health and nutritional status of children.